THE PAGAN BELIEFS AND THE SACRED: PERMANENT ISOTOPIES AND INTERSUBJECTIVITIES IN THE CARNIVAL LITANIES OF BARRANQUILLA - Espinosa Patrón, Alejandro (2019)
The research on the pagan beliefs as a performative and intersubjective act in the carnival litanies of Barranquilla, Colombia, had the purpose of identifying how the pagan beliefs become an isotopy that go through the texts of the speeches of carnival litanies. The litanies from his speech establish a permanent criticism through texts that reflect a new way of communicating, multimodal from Kress & Leeuwen. For the development of the study, a qualitative deductive and analytic-deductive research was done, because it was based on the description of each one of the three litanies analyzed.